1999
DOI: 10.1002/(sici)1521-3935(19990601)200:6<1306::aid-macp1306>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of copolymers of ethylene and 1-octadecene using therac-Et(Ind)2ZrCl2/MAO catalyst system

Abstract: The copolymerization of ethylene and 1‐octadecene using a bridged metallocene was studied in order to observe the effect of the comonomer on the catalytic activity. A noticeable increase in activity is seen as the concentration of 1‐octadecene in the reaction medium increases. 13C NMR analysis shows 6.4 mol‐% incorporation of comonomer at the highest 1‐octadecene concentration in the feed used here. The molecular weight of the copolymers shows a drastic decrease that may be attributed to chain termination by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 0 publications
5
31
0
Order By: Relevance
“…[22] These catalyst precursors were chosen since iron catalyst 20 is highly selective for the production of 1-alkenes, [23] and metallocenes 21 and 3 are known for their ability to copolymerize ethylene and higher 1-olefins. [24] The polymerization reaction performed in toluene at 60 8C using an Al/Fe molar ratio of 2 000 showed that increasing the Fe/Zr ratio leads to a reduction in productivity. 13 C NMR data revealed that the degree of branching increased with increasing Fe/Zr ratio.…”
Section: Ethylene Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] These catalyst precursors were chosen since iron catalyst 20 is highly selective for the production of 1-alkenes, [23] and metallocenes 21 and 3 are known for their ability to copolymerize ethylene and higher 1-olefins. [24] The polymerization reaction performed in toluene at 60 8C using an Al/Fe molar ratio of 2 000 showed that increasing the Fe/Zr ratio leads to a reduction in productivity. 13 C NMR data revealed that the degree of branching increased with increasing Fe/Zr ratio.…”
Section: Ethylene Polymerizationmentioning
confidence: 99%
“…Additional studies with respect to the production of stereoblock poly(propylene) by using in-situ mixtures of metallocene catalysts with different stereoselectivity were recently performed by Brintzinger et al [28] Propene polymerization reactions were performed using metallocene catalysts 22, Me 2 Si(2-Me-4-t Bu-C 5 H 2 ) 2 ZrCl 2 (24) and Me 2 Si(2-MeInd) 2 ZrCl 2 (25) in the presence of either MAO or triisobutylaluminium (Al i Bu 3 )/triphenylcarbenium tetrakis(perfluorophenylborate) ([Ph 3 C][B(C 6 F 5 ) 4 ], trityl borate) as the cocatalyst.…”
Section: Propene Polymerizationmentioning
confidence: 99%
“…Isotactic poly(propylene)-co-hexenes of varying comonomer incorporation, PP6-A and PP6-B, were synthesised using the metallocene rac-[Me 2 Si(2-Me-Ind) 2 ]ZrCl 2 catalyst and MAO cocatalyst. [45] Melt-state NMR was performed on three dedicated solidstate Bruker Avance NMR spectrometers: a narrow-bore DRX700, a wide-bore DSX500 and a wide-bore DSX300. These operated at 1 H and 13 C Larmor frequencies n 1 H (n 13 C ) of 700.13 (176.05), 500.13 (125.75) and 300.23 (75.49) MHz respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The activity decreased while the 9D1O feeding amount increased (run 5-7). The so-called 'comonomer effect' has been observed in several manners for the ethylene copolymerization with α-olefin [30,31]. The incorporation of 9D1O into the polymer chain improved the solubility of the resulteding polymer in the reaction mixture; therefore the resistance of the mass and heat transfer would be reduced, leading to the increased activity.…”
Section: Resultsmentioning
confidence: 99%